The Effects of State Merit Aid Programs on Attendance at Elite Colleges - David L. Sjoquist; John V. Winters (Institute for the Study of Labor (IZA), 2015)
State merit aid programs have been found to reduce the likelihood that students attend college out-of-state. Using the U.S. News & World Report rankings of colleges and universities to measure college quality and Integrated Postsecondary Education Data System data to measure enrollment, we explore how this reduction in out-of-state enrollment differs by the academic quality of the institution. Our results suggest that state merit aid programs do not reduce the likelihood that a student attends a top ranked school, but that these programs do reduce the likelihood of enrolling at less prestigious out-of-state schools, with generally larger effects the lower the ranking of the schools.
Keywords: H31; I22; J24; 330; merit aid; college choice; college quality; elite college